2022
DOI: 10.1002/ijgo.14080
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of obstetric fistula in Afghanistan: An analysis of the Demographic and Health Survey 2015

Abstract: Objective To examine the reproductive, sociodemographic, and geographic factors associated with obstetric fistula, which is a significant but neglected health problem faced by women in low‐income countries, in women in Afghanistan, where epidemiologic studies examining the determinants of obstetric fistula are currently lacking. Methods This cross‐sectional study used data from a nationally representative sample of women collected through the Afghanistan Demographic and Health Survey 2015. Descriptive and bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…9 Studies based on the 2015 Afghanistan Demographic and Health Survey support that SRHR outcomes ranging from the rate of domestic violence, access to antenatal care, to the occurrence of obstetric fistula are associated with systemic challenges such as low literacy, lack of empowerment, and poverty. [10][11][12][13] This suggest that the consequences of too many pregnancies cannot be mitigated by one health initiative alone but requires a comprehensive approach including sexual education for girls and boys, the prevention of coerced or child marriage, informed contraceptive choice, the legal and structural prerequisites for safe abortion, counseling for rape, as well as antenatal, peripartum, and postpartum care including contraceptive counseling. Poverty reduction and sustainable development are intrinsically linked to SRHR through the provision of reproductive autonomy for women, usually resulting in smaller and more resourceful families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Studies based on the 2015 Afghanistan Demographic and Health Survey support that SRHR outcomes ranging from the rate of domestic violence, access to antenatal care, to the occurrence of obstetric fistula are associated with systemic challenges such as low literacy, lack of empowerment, and poverty. [10][11][12][13] This suggest that the consequences of too many pregnancies cannot be mitigated by one health initiative alone but requires a comprehensive approach including sexual education for girls and boys, the prevention of coerced or child marriage, informed contraceptive choice, the legal and structural prerequisites for safe abortion, counseling for rape, as well as antenatal, peripartum, and postpartum care including contraceptive counseling. Poverty reduction and sustainable development are intrinsically linked to SRHR through the provision of reproductive autonomy for women, usually resulting in smaller and more resourceful families.…”
Section: Discussionmentioning
confidence: 99%
“…A study from prior to the regime change identified similar structural barriers to access to care 9 . Studies based on the 2015 Afghanistan Demographic and Health Survey support that SRHR outcomes ranging from the rate of domestic violence, access to antenatal care, to the occurrence of obstetric fistula are associated with systemic challenges such as low literacy, lack of empowerment, and poverty 10‐13 …”
Section: Discussionmentioning
confidence: 99%